2019
DOI: 10.1021/acsanm.9b00037
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous ZSM-5 Crystals Coated with Silicalite-1 for Enhanced p-Xylene Separation

Abstract: The growth of a silicalite-1 coating on ZSM-5 zeolite crystals is one of the surface modification methods allowing to improve its catalytic p-xylene selectivity. Aiming to understand this increase in p-xylene selectivity, the effect of silicalite-1 coating on the adsorptive properties of ZSM-5 was investigated. Pulse chromatographic experiments revealed the silicalite-1 coating improved the separation factors of p-xylene over o-xylene and m-xylene, resulting in a better chromatographic separation of p-xylene o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…But the proportions of the content of A9 and A10+ showed the opposite trend. Considering that the pore size of HZSM-5 (0.53 × 0.56 and 0.51 × 0.55 nm) was similar to the kinetic diameter of A8 (around 0.58 nm), , it was speculated that increasing the L/B could better utilize the pore selectivity of HZSM-5 without seriously affecting the catalyst pore size. However, when the loading content of Zn was too high (above 3 wt %), the pore size was reduced and the pore channel was blocked.…”
Section: Resultsmentioning
confidence: 97%
“…But the proportions of the content of A9 and A10+ showed the opposite trend. Considering that the pore size of HZSM-5 (0.53 × 0.56 and 0.51 × 0.55 nm) was similar to the kinetic diameter of A8 (around 0.58 nm), , it was speculated that increasing the L/B could better utilize the pore selectivity of HZSM-5 without seriously affecting the catalyst pore size. However, when the loading content of Zn was too high (above 3 wt %), the pore size was reduced and the pore channel was blocked.…”
Section: Resultsmentioning
confidence: 97%
“…The improvement in BTX selectivity demonstrated that the secondary reaction of products was inhibited due to the surface modification of ZSM-5, which was consistent with the previous studies. 32 Furthermore, the catalyst stability of the modified samples was studied, as shown in Figure 5b. Not all the modified samples have improved the catalyst stability, following ZSM-5-M1 > ZSM-5-P > ZSM-5-M2 > ZSM-5-M3, which was inconsistent with the previous studies on the external acidity.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In addition, the zeolite framework can be decorated by various elements with the valency ranging from I to V including B, K, Sn, and Ga, as well as transition metals such as Ce, Fe, Mn, Co, Zn, and Cu. , Therefore, these materials can be synthesized with favorable properties, for instance, desirable porous structures, the appropriate Si/Al ratio, and a suitable cation type. Because of the advantageous characteristics of zeolites, including less toxicity, large surface area, molecular shape selectivity and adsorption capacity for guest molecules, and good thermal and chemical stabilities, they have been utilized in many potential applications, for example, ion-exchange, adsorption, separation, , and especially catalysis. , …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Therefore, these materials can be synthesized with favorable properties, for instance, desirable porous structures, the appropriate Si/Al ratio, and a suitable cation type. Because of the advantageous characteristics of zeolites, including less toxicity, large surface area, molecular shape selectivity and adsorption capacity for guest molecules, and good thermal and chemical stabilities, 3 they have been utilized in many potential applications, for example, ion-exchange, 4 adsorption, 5 separation, 6,7 and especially catalysis. 8,9 To date, zeolites have been extensively used as heterogeneous catalysts in the refinery and petrochemical processes because of their superior properties involving the shapeselective properties and the suitable acidity.…”
Section: Introductionmentioning
confidence: 99%